Camcorder generation: the first videographic cycle in Espírito Santo - Guimarães , Ernandes Zanon (Farol, 2022)
This article analyzes the videographic production process in the 1980s in Vitória, Espírito Santo, based on the first experiments carried out by the Balão Mágico cultural movement at the Federal University of Espírito Santo (UFES). This pioneering initiative, focused on exploring video as a means of artistic expression, marked the introduction of videography in Vitória and boosted an intense audiovisual production, later known as the first videographic cycle in Espírito Santo.